Preliminary Fault tree Analysis of Landing Gear Control and Warning for LSA 02 Motorized Glider Type Aircraft - Wirawan, Adi; Pranoto, Fuad Surastyo (BRIN Publishing, 2021)
In this paper, the authors present an approach of reliability analysis to analyze the landing gear control and warning system, which is planned to be installed on LSA-02 aircraft. The reliability analysis will use fault tree analysis as starting point to investigate what is the top undesired event which might occur in this system. The construction of causal tree analysis offers a framework privileged to the deductive analysis, which consists of seeking the various possible combinations of events, leading to the occurrence of a top undesired event. The fault tree analysis shows that the top undesired event for this system is when the landing gear is commanded to extended, the system fails to extend the landing gear, and warning system is failed to operate.